O paraíso extraviado: elementos neo-utópicos e distópicos em Pessach, A travessia, A festa e A terceira margem - Sarmento-Pantoja, Tânia Maria Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2005)
This research is essentially based on the idea that every object of culture is also an object of barbarism, as Walter Benjamin thinks. In this way, the analyzed corpus, composed by the novels Pessach, a Travessia, A Festa and A Terceira Margem, are understood as narratives that testify permanent violations, expressed in various forms, in addition to dialoguing intertextually with historical references marked by violence, especially violence resulting from repression produced by the exception state. The governability of the state of exception and its repressive character is an important formulation for the understanding of the narrative economy of the three novels analyzed. These novels are also profoundly marked by a change in experience with time itself and thus in the aesthetic dimension: in working with representation. This aesthetic dimension accompanies the broad dislocations of the utopian energies that compose them. Energies that decompose or progress to dystopian and / or neo-utopian energies. In considering these aspects we raise the following thesis: if dystopia is an important narrative element with narratological and also aesthetic function of emphasizing the violation, due to an authoritarian regime of governability, which is present in the three narratives, based on the dialogue intertextual with historiography and with the culture related to the state of exception, how the integration of the dystopic elements – and, on the contrary, the utopian elements – penetrate the transformations undergone by the post-dictatorial Brazilian novel? In order to demonstrate this thesis we produced a corpus analysis, based on a case study, in association with investigations carried out by historians, especially those elaborated by Marcelo Ridenti (2000) and Carlos Fico (1997; 2004) with theories about utopia, dystopia and neo-utopia; and with the corpus of studies of literary criticism on Brazilian fiction, which questioned the state of exception established in Brazil between the 60s and 80s of the 20th century.

Esta investigación se basa esencialmente en la idea de que todo objeto de cultura es también un objeto de la barbarie, como piensa Walter Benjamin. De este modo, el corpus analizado, compuesto por las novelas Pessach, a Travessia, A Festa y A Terceira Margem, son entendidos como narrativas que testimonian permanentes violaciones, expresadas de variadas formas, además de dialogar intertextualmente con referencias históricas marcadas por la violencia, especialmente la violencia resultante de la represión producida por el estado de excepción. La gobernabilidad del estado de excepción y su carácter represor es una formulación importante para la comprensión de la economía narrativa de las tres novelas analizadas. Estas romances también están profundamente marcados por un cambio en la experiencia con el propio tiempo y, por lo tanto, en la dimensión estética: en el trabajo con la representación. Esta dimensión estética acompaña los amplios desplazamientos de las energías utópicas que los componen. Energías que se descomponen o progresan hacia energías distópicas y / o neo-utópicas. Al considerar estos aspectos planteamos la siguiente tesis: si la distopía es un elemento narrativo importante con función narratológica y también estética de dar énfasis a la violación, en función de un régimen de gobernabilidad autoritario, que se muestra presente en las tres narrativas, con base en el diálogo intertextual con la historiografía y con la cultura relacionada al estado de excepción, de qué modo la integración de los elementos distópicos – y, por oposición, los utópicos – penetran las transformaciones sufridas por la novela post-dictatorial brasileña? Para demostrar esta tesis producimos un análisis del corpus, basado en un estudio de caso, en asociación con investigaciones realizadas por historiadores, especialmente aquellos elaborados por Marcelo Ridenti (2000) y Carlos Fico (1997; 2004); con teorías sobre la utopía, la distopía y la neo-utopía; y con el corpus de estudios de crítica literaria sobre la ficción brasileña, que cuestionó el estado de excepción instaurado en Brasil, entre las décadas de 60 y 80, del Siglo XX.

Esta pesquisa se baseia, essencialmente, na ideia de que todo objeto de cultura é também um objeto da barbárie, conforme pensa Walter Benjamin. Desse modo, o corpus analisado, composto pelos romances Pessach, a Travessia, A Festa e A Terceira Margem, são entendidos como narrativas pós-ditatoriais que testemunham permanentes violações, expressadas de variadas formas, além de dialogarem intertextualmente com referências históricas marcadas pela violência, especialmente a violência resultante da repressão produzida pelo estado de exceção. A governabilidade do estado de exceção e seu caráter repressor é uma formulação importante para a compreensão da economia narrativa dos três romances analisados. Esses romances são também profundamente marcados por uma mudança na experiência com o próprio tempo e, portanto, na dimensão estética: no trabalho com a representação. Essa dimensão estética acompanha os amplos deslocamentos das energias utópicas que os compõem. Energias que se decompõem ou progridem para energias distópicas e/ou neo-utópicas. Ao considerar esses aspectos levantamos a seguinte tese: se a distopia é um elemento narrativo importante com função narratológica e também estética de dar ênfase à violação, em função de um regime de governabilidade autoritário, que se mostra presente nas três narrativas, com base no diálogo intertextual com a historiografia e com a cultura relacionada ao estado de exceção, de que modo a integração dos elementos distópicos – e, por oposição, os utópicos – penetram as transformações sofridas pelo romance pós-ditatorial brasileiro? Para demonstrar esta tese produzimos uma análise do corpus, baseada em estudo de caso, em associação com investigações realizadas por historiadores, especialmente aqueles elaborados por Marcelo Ridenti (2000) e Carlos Fico (1997; 2004); com teorias sobre a utopia, a distopia e a neo-utopia; e com o corpus de estudos de crítica literária sobre a ficção brasileira, que questionou o estado de exceção instaurado no Brasil, entre as décadas de 60 e 80, do Século XX.
The lost paradise: neo-utopian and dystopian elements in Pessach, A travessia, A festa and A terceira margem
Keywords: Romance Pós-Ditatorial; Utopia; Distopia; Neo-Utopia; Resistência; Violência política; Post-dictatorial Romance; Utopia; Dystopia; Neo-utopia; Resistance; Romance post-dictatorial; Utopía; Distopía; Neo-utopía